Analysis of the Development of Ecotourism at Sirukam Dairy Farm in Sirukam Village, Alahan Panjang, Solok Regency, West Sumatra - Puti Tiara Dewi; Siti Fatimah; Ratna Wilis (Sumatra Journal of Disaster, Geography and Geography Education, 2025)
This study aims to analyze the development of Sirukam Dairy Farm ecotourism in Sirukam Village, Alahan Panjang, Solok Regency, West Sumatra. This study uses SWOT analysis to describe the internal and external environments that constitute the strengths, weaknesses, opportunities, and threats of Sirukam Dairy Farm ecotourism. The results show that a dairy farm such as Sirukam Dairy Farm in Solok Regency has great potential to be developed into an ecotourism destination, utilizing the appeal of rural life, the milk production process, and the beauty of the surrounding nature. In addition to dairy farming, there are also other types of farming such as sheep, rabbits, chickens, and many more. Based on the results of the internal research, the strengths of Sirukam Dairy Farm ecotourism are greater than its weaknesses, with an IFAS score of 3.34 compared to a weakness score of 2.58. Meanwhile, from an external perspective, the opportunities are smaller than the threats, with an EFAS score of 3.04 compared to an opportunity score of 3.01. Therefore, it is evident that the opportunities and threats are quite similar. The results of the SWOT analysis suggest that Sirukam Dairy Farm ecotourism is located in Quadrant II, indicating that although it encounters threats, it still has the capability to leverage long-term opportunities by implementing strategies like diversifying attractions centered around education and recreation.